(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As the world faces the challenges of feeding a growing global population while minimizing the environmental impact of agriculture, precision agriculture emerges as a pivotal solution. This article explores the intersection of precision agriculture and sustainable development with a primary emphasis on the transformative power of machine learning. Precision agriculture leverages data-driven techniques and technology to optimize farming practices, reduce resource wastage, and enhance crop productivity. Within this framework, machine learning algorithms play a critical role in real-time data analysis, predictive modeling, and decision support systems. This paper delves into the various applications of machine learning in agriculture, including soil health management, crop monitoring, pest and disease detection, and resource efficiency. The synergy between precision agriculture and machine learning offers a promising pathway toward sustainable farming practices, ensuring food security while minimizing the ecological footprint. By understanding the potential of machine learning in precision agriculture, we can pave the way for a more sustainable and resilient future in food agriculture.